(untitled) (Tribhuvan University Journal of Microbiology, 2020)
Objectives: Acquisition of mecA gene in infectious strains of Methicillin resistant Staphylococcus aureus (MRSA) are considered as one of the potential virulence factors that enables the host bacteria to carry out several nosocomial and community-acquired infections. The main aim of this study was to determine the prevalence of MRSA, their antibiogram and mecA gene in the bacterial isolates obtained from the asymptomatic healthcare workers (HCWs) working in Sukraraj Tropical and Infectious Disease Hospital (STIDH), Kathmandu Nepal. Methods: This prospective cross-sectional study involved the collection of nasal and hands swab of 125 randomly selected HCWs from December 2019 to February 2020. Conventional microbiological methods were used to isolate and identify S. aureus. Antimicrobial susceptibility testing was done by modified Kirby Bauer disc diffusion method. MRSA was confirmed by using cefoxitin disc. Detection of mecA gene in the chromosome which was extracted by Phenol: Chloroform: isoamyl alcohol DNA extraction method, amplified by using PCR and visualized by running agarose gel electrophoresis. Results: The overall and MRSA carriage rate among the HCWs was found to be 28% (35/125) and 10.4% (13/125) respectively. S. aureus carriage rate was highest among sanitation staffs (34.2%) followed by pharmacy staffs (33.3%), laboratory personnel (18.8%), doctors (9.1%) and nurses (7.5%). Similarly, 34.2% (13/38) of the S. aureus isolates were resistant to methicillin, 31.6% (12/38) were inducible-clindamycin resistant and 63.2% (24/38) of them were multi-drug resistant (MDR). All the 13 MRSA isolates harbored the mecA gene. Conclusions: Carriage rate of MRSA among HCWs was high and alarming, indicating the prompt need of intervention measures to curb the growth and spread of resistant isolates in the hospital settings. Effective surveillance (of infectious diseases) and establishment of advanced diagnostic facilities can assist in estimating the actual burden of the MRSA which in turn helps to formulate and implement the appropriate policies and infection-control programs to address the increasing antimicrobial resistance in the country.